COMPARATIVE ASSESSMENT OF FIBER BASES FOR THE MANUFACTURE OF COMPOSITE MATERIALS WITH SORPTION PROPERTIES - ПЛАВАН, В. П.; ІЩЕНКО, О. В.; ТИТАРЕНКО, С.; СІДЕЛЬНІКОВ, Я.; ТАРАСЕНКО, Н. В. (Technologies and Engineering, 2024)
Purpose. Comparative analysis of two types of fibrous bases for the production of composite materials with sorption properties by impregnation of the fibrous base by filled dispersions of water-soluble polymers. Methodology. As a basis for obtaining the fibrous sorbents, the following fibrous bases were used in the work: needle-punched non-woven material with a surface density of 227 g/m2 (PU/PA-6.6), obtained from waste polyurethane-polyamide chemical fibers. It consists of Lycra 162C complex fibers (linear density 4.4 tex) (PU) and Nylon 6.6 f20/1 fibers (linear density 3.3 tex) (PA-6.6) in a ratio of 70/30 by weight. %. Non-woven material from polyester microfibers obtained by the aerodynamic method with a surface density of 178 g/m2 (PET). Montmorillonite-type clay powder was added to the composite materials in the range of 5 to 10% of the total mass of the material. Filled dispersions of water-soluble polymers of PVA and starch were used to impregnate the fibrous base. The influence of the concentration of polymer solutions and the amount of introduced adsorbent on the moisture absorption and vapor permeability of materials was studied in accordance with ISO 20158:2018 and ISO 15496:2018, and the characteristics of the mechanical properties of nonwoven materials when stretched on a tearing machine type RM-30 were determined, in accordance with the DSTU standard ISO 9073-3:2003. Findings. It was established that an increase in the concentration of the polymer binder leads to a compaction of the structure of the fibrous base and, as a result, to an increase in its surface density. Also, the surface density is affected by the amount of mineral sorbent: the introduction of 5% clay leads to a more than twice increase in surface density, and with 10% clay, the surface density increases almost twice. With an increase in the concentration of water-soluble polymers and the content of clay in the dispersion, the moisture absorption of all types of non-woven materials decreases somewhat. The physical and mechanical properties of fibrous materials depend on the type of initial fiber, the type and concentration of the polymer binder, and the amount of clay adsorbent introduced. An increase in the concentration of the PVA solution leads to an increase in the strength of the impregnated fibrous base of both PU/PA-6.6 and PET, but causes a decrease in the relative elongation at break. The loss of elasticity of materials occurs as a result of structuring, and the degree of structuring is higher in the case of the use of filled PVA dispersions. Originality. The use of two different types of non-woven materials with different structure and composition, impregnated with filled dispersions of water-soluble polymers, which can later be used to obtain fibrous composite materials with sorption properties. Practical value. Composite materials with sorption properties, based on fibrous waste, can be used in the future for the purification of wastewater from light and chemical industry enterprises from heavy metal ions.